Job Satisfaction Among Health Workers at Primary Health Care in Palembang City, Indonesia - Ainy, Asmaripa; Sarri, Merri Nurmala; Fujiyanti, Poppy; Inaku, Hartati; Tembo, Tannia (UI Scholars Hub, 2025)
Health workers at primary health care are the frontline providers of community health services. This study aimed to investigate the level of job satisfaction of health workers at primary health care in Palembang City, South Sumatra Province, Indonesia, and its influencing factors. Using a questionnaire developed by the authors' team, the study involved 257 samples. A total of 66.15% of respondents indicated high satisfaction, 21.79% reported moderate satisfaction, and 12.06% expressed dissatisfaction. A statistically significant correlation was found between knowledge, skills, income, promotion opportunities, work supervision, and relationships with colleagues and job satisfaction (p-value <0.001). The correlations were strong, with Spearman's rho of 0.822, 0.869, 0.912, 0.895, and 0.821, respectively. Statistical analysis of the Wilcoxon rank-sum and Kruskal-Wallis tests showed no significant differences in median satisfaction scores between sociodemographic groups (p-value 0.072 to 0.552>0.05). These findings showed that job satisfaction depends on multiple factors. Both intrinsic and extrinsic factors play a key role in shaping job satisfaction. Health workforce management should prioritize organizational factors to sustain job satisfaction over sociodemographic factors. Key strategies include regular training, fair salaries, clear promotion paths, strong supervision, and fostering teamwork through leadership training and staff meetings.